MeL2Zn2(μ-1, 6-Ph2-N6) – a building block for new hexazene complexes12. Issue 35 (21st September 2015) - Gondzik, S.; Wölper, C.; Haack, R.; Jansen, G.; Schulz, S.
<x xml:space="preserve">Abstract</x> MeL2Zn2(μ-1, 6-Ph2-N6) 1 (MeL = HC[C(Me)N(2, 4, 6-Me3C6H2)]2) serves as hexazene transfer reagent in reactions with main group metal and transition metal complexes containing M–Me units.